2013
DOI: 10.1186/1868-7083-5-20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of IGFBP-7 DNA methylation changes and serum protein variation in Swedish subjects with and without type 2 diabetes

Abstract: Background: Insulin-like growth factor-binding protein 7 (IGFBP-7) is able to interact with insulin-like growth factor 1 (IGF-1) as well as insulin. Previous studies have suggested that serum IGFBP-7 levels may be associated with insulin resistance in type 2 diabetes (T2D). This study aimed to evaluate IGFBP-7 serum protein and IGFBP7 DNA methylation levels in the subjects with and without T2D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 37 publications
0
37
2
1
Order By: Relevance
“…Also IGFBP7 has been linked to insulin resistance and Type 2 diabetes, and is further able to interact both with insulin and insulin-like growth factor-1. In a similar approach as above, Gu et al found increased IGFBP7 DNA methylation in men newly diagnosed with Type 2 diabetes, however, no correlation with serum IGFBP7 protein levels was observed [37].…”
Section: Epigenetic Alterations and Insulin Sensitivitymentioning
confidence: 95%
See 1 more Smart Citation
“…Also IGFBP7 has been linked to insulin resistance and Type 2 diabetes, and is further able to interact both with insulin and insulin-like growth factor-1. In a similar approach as above, Gu et al found increased IGFBP7 DNA methylation in men newly diagnosed with Type 2 diabetes, however, no correlation with serum IGFBP7 protein levels was observed [37].…”
Section: Epigenetic Alterations and Insulin Sensitivitymentioning
confidence: 95%
“…However, to be useful as a clinical biomarker, it is also essential to find markers that are reflected in readily accessible tissues or cells, such as blood samples. A few Type 2 diabetes case-control studies have investigated epigenetic alteration in Type 2 diabetes candidate genes in blood samples [35][36][37][38][39]. Toperoff et al detected differentially methylated regions (DMRs) in blood from patients with Type 2 diabetes compared with control individuals, including 6 DMRs in regions previous genetically associated with Type 2 diabetes (CENTD2, FTO, KCNJ11, TCF7L2 and WFS1) [39].…”
Section: Evidence Of Epigenetic Alterations Of Genes Involved In Insumentioning
confidence: 99%
“…In recent years, we have carried out epigenetic studies of the insulin-like growth factors (IGF-I and IGF-II) and their binding proteins (IGFBPs) in diabetes [5][6][7]. IGFBP-2 is the second most abundant circulating IGFBP and expressed by the liver and white adipose tissue [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…As a special member of the IGFBP family, IGFBP7 is commonly considered as a tumour suppressor in various human malignancies, such as lung, colon, liver and pancreatic cancers . Recently, higher serum concentrations of IGFBP7 and IGFBP7 DNA methylation levels have been considered as an increasing risk factor for the development of type 2 diabetes . Lopez‐Bermejo et al suggested that serum IGFBP7 was closely related to body mass index (BMI) in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%